ANALISA PERHITUNGAN HARGA POKOK PRODUKSI DALAM PENENTUAN HARGA JUAL PADA PT. HEXING TECHNOLOGY - Bintang Harapan; Lorina Siregar Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
PT. Hexing Technology is an Indonesia-based electronic metering and system company that was founded in 2009. The calculation of the cost of production and the determination of the company's selling price is very important in classifying costs. The purpose of this study was to determine the calculation of the cost of production at PT. Hexing technology which aims to obtain a clear picture of the method of calculating the cost of production and selling price used by the company. The results of this study are that there are differences in the calculation of the cost of production applied by the company using the mark up pricing method and the calculation carried out by the researcher on the cost of production using the job order costing method. This is because the calculation of the cost of goods manufactured by the company or using the mark-up method so far does not take into account all factory overhead costs that should be charged. then the results of this study by using job order costing get a bigger profit.